URGENSI RUU PENGHAPUSAN KEKERASAN SEKSUAL (RUU PKS) TERHADAP KEKERASAN DALAM RUMAH TANGGA - Safitri Wikan (Pahlawan, 2021)
The purpose of this study was to determine whether there is an effect of the urgency of the Draft Law on the Elimination of Sexual Violence against domestic violence, more specifically sexual violence in the household, where there has been a Domestic Violence Law which regulates it. Law Number 23 of 2004 concerning the Elimination of Domestic Violence is not a special rule intended to accommodate and resolve problems of sexual violence. Moreover, as the name implies, Law Number 23 of 2004 concerning the Elimination of Domestic Violence only applies if the violence occurs within the household. When viewed from the urgency of sexual violence in the household, even though the draft law will overlap the rules against crimes of sexual violence in the household, but if the Draft Law on the Elimination of Sexual Violence is passed, it will be an alternative indictment for law enforcement officers in trapping perpetrators of sexual violence crimes. It is expected that the Draft Law on the Elimination of Sexual Violence is passed into law. So that it can ensnare the perpetrators of sexual violence crimes, even though in other laws there are already regulated but the Law which specifically provides protection against crimes of sexual violence is highly anticipated, especially for women and children who are vulnerable to the crime.